Fungal spore concentrations in the atmosphere at the Anatolia quarter of Istanbul, Turkey - ÇOLAKOĞLU, GÜNAY TÜLAY (AKADEMIE VERLAG GMBH, 1996)
In this research, spore concentrations of Cladosporium, Alternaria, Epicoccum, Botrytis, Leptosphaeria, Polythrincium, ascospores, Aspergillus, Penicillium, basidiospores, uredospores, Ustilago, Torula, Erysiphe, Ganoderma, Hyaline indeterminate and others in the atmosphere have been determined, and comparisons have been made between locations with both low and high spore concentrations. The importance of these air-borne fungal spores which cause allergy and asthma are emphasized in the paper from the viewpoint of human health. This study describes observations on the concentrations in which fungal spores occur in the air at the Anatolia Quarter of Istanbul, Turkey and discuss their origins. We are interested in the development of inhalant allergy in populations residing in the area.
Keywords: ALLERGY